EKSPRESI KEBERAGAMAN DI LOKASI WISATA RELIGI PONPES TEBUIRENG JOMBANG (PERSPEKTIF ETNOLINGUISTIK) - Bambang Hariyanto (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2015)
This article aims at describing of pattern and social style at the religioustourism object at Ponpes Tebuireng (cottage) to explore the language fact in the social interaction. Furthermore, by exploring interaction here can give more understanding which is done by the society without blaming to their activities. This research is done based on Spradley theories (1997) entitle ethnography communication method. In addition, for data analysis using Sudaryanto theories’ (1995) because this paper as qualitative research. Then, the data classified and analysed based on the role and it functions.The result of this research shows that there are several things for thepeople who visits the graveyard of Tebuireng. There are three main kinds of the visitor; they are Santri, Abangan, and Non-Moslem people. Related to verbal communication consists of opening, content and closing. The three aspect of verbal communication of this happened to Santri, Abangan and Non-Moslem people. For non-verbal aspects, Santri groups usually wear songkok. Then for Abangan, they usually wear Javanese traditional clothes and for Non-Muslim people they wear based on their believer or their clothes.Keywords: Ethnolinguistics, local wisdom, tradition